Pursuing claims under unfair contract terms on the basis of undue performance provisions - Nycz, Maciej Aureliusz (The Opole Studies in Administration and Law, 2020)
The article deals with the mutual relations between wrongful contractual provisions (unfair clauses) and undue performance. The former was introduced into the Polish civil law by an amendment made to the Polish Civil Code in connection with the 93/13/EC Directive entry into force. In turn, the institution of undue performance has long been recognised in Poland as the method of pursuing claims under the unfair clauses. Mutual relations of provisions pertaining to the above-mentioned notions still have not been thoroughly examined. Nonetheless, the simultaneous analysis of the provisions reinforces the statement that the undue performance claim may be useful in pursuing claims for enrichment arising from performance of service based on unfair clauses. To be exact, condictio indebiti claim shall be invoked to successfully pursue the claim. On the other hand, only a few scholars and courts deem so. The reason why this type of undue performance claim is applied lies within the pain of ineffectiveness for setting forth unfair clauses. Moreover, the provisions ought to be interpreted in a way that reflects the European Union law application.